Should we describe genera without molecular phylogenies? - Páll-Gergely, Barna (Zootaxa, 2017)
For nearly a decade I have published species descriptions and revisions of land snails in peer- reviewed journals. As a systematist, it is often requisite to reclassify species into other, sometimes unnamed genera. Although in most cases editors and reviewers have not commented on the taxonomic changes I have made and the new taxa I described, I sometimes received negative critiques when I described new genera unaided by molecular phylogenetic support. I feel these critiques have become increasingly more frequent, and am convinced that many fellow taxonomists share this experience. Addressing this problem is particularly difficult due to three reasons. First, it is impossible to support these observations with statistical data (i.e. the frequency of similar reviews increasing or not); second, the increasing number of published phylogenetic works reveals more and more cases of polyphyletic genera, which might suggest that morphology-based generic grouping is unreliable, and thus, should be avoided; and third, no publications exist suggesting not to describe genera using (still) reliable morphological foundations. Subsequently, the unsatisfactory review process of taxonomic works is often exacerbated by the biases of reviewers and their inobservance of valuable historic convention in light of the current wave of molecular phylogenies. Moreover, the future value of morphological descriptions for biodiversity assessments (i.e. IUCN) is not even addressed.